2022
DOI: 10.21037/tlcr-22-444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a three-gene expression signature and construction of a prognostic nomogram predicting overall survival in lung adenocarcinoma based on TCGA and GEO databases

Abstract: Background: Lung adenocarcinoma (LUAD) is the major cause of cancer mortality. Traditional prognostic factors have limited importance after including other parameters. Thus, developing a more credible prognostic model combined with genes and clinical parameters is necessary. Methods:The messenger RNA (mRNA) expression and clinical information from The Cancer Genome Atlas (TCGA)-LUAD datasets and microarray data from three Gene Expression Omnibus (GEO) databases were obtained. We identified differentially-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Gene expression signatures have been widely used in research to evaluate OS in LUAD [ 15 , 16 , 17 , 18 , 19 , 20 , 28 ]. For example, Zhou et al established a three-gene signature that achieved a C-index of 0.638 in TCGA-LUAD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression signatures have been widely used in research to evaluate OS in LUAD [ 15 , 16 , 17 , 18 , 19 , 20 , 28 ]. For example, Zhou et al established a three-gene signature that achieved a C-index of 0.638 in TCGA-LUAD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression signatures have been widely used in research to evaluate OS in LUAD [ 15 , 16 , 17 , 18 , 19 , 20 , 28 ]. For example, Zhou et al established a three-gene signature that achieved a C-index of 0.638 in TCGA-LUAD [ 28 ]. Through Kaplan–Meier analysis, we further confirmed that gene expression could effectively classify patients into high- and low-risk groups using KMeans clustering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the explosion of sequencing data and bioinformatics have opened up the possibility of precision therapy. More and more predictive signatures are being developed to provide ideas for clinical immunotherapy and targeted therapies (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%